Gestão de pessoas na Procuradoria Geral do Município do Rio de Janeiro - Ferreira, Lucio Almirão (2009)
This study aimed to verify the type of Personnel Management adopted during the period between January 2005 and December 2008 at the Municipal General Attorney¿s Office (PGM-RJ) is compatible with the challenges of society and management people in the twenty-first century and why. To enable this conclusion, the means used were the research literature, documentary and field, through a process of self-ethnography. The literature review presented the evolutionary process and culture of public administration in Brazil, the new challenges of society and people management in the twenty-first century, the evolutionary process of managing people and its main approaches and models. The field research provided data wich related to them with the literature review, allowed to identify the predominant features of public administration and culture of PGM-RJ and the people management approaches identified. In addition, the study highlights that despite the effort in making changes and advances in the use of many different ideas of functionalist approach, the human resource practices adopted in the PGM-RJ during the period between January 2005 and December 2008 were not fully compatible with the challenges of society and people management in the twenty-first century.